The Influence of The Training Program on The Knowledge of Posyandu Cadres in The Department of Women's Empowerment, Child Protection and The Community of Binjai City - Aswansari, Ruri; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
The aim of this research is to determine and analyze the influence of training on knowledge among Posyandu cadres for employees of the Binjai City Women's Empowerment, Child and Community Protection (DP3AM) Service. This research was carried out at the Women's Empowerment, Child Protection and Community Service (DP3AM) Binjai City. The type of research is associative quantitative. The sample in this study was 172 Posyandu Cadres from the Women's Empowerment, Child and Community Protection Service (DP3AM) of Binjai City. The sampling technique in this study used a random sampling technique from the entire population of 1205 people. The research results show that training has a significant influence on knowledge as shown by the t value of 16.606 > t table 1.653 and the P value of 0.000 < 0.05. This shows that improvements in training can increase the knowledge of Posyandu cadres at the Binjai City Women's Empowerment, Child Protection and Community (DP3AM) Service.